FLECHA: a Forecasting eLEction meCHAnism for semantic collectors sensor nodes - M. Neto, Mauricio; Moreira, Leonardo O.; Gomes, Danielo G. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2016: Anais do XV Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2016)
Due to the resource constraints of the sensor nodes, energy provisioning in wireless sensor networks remains a challenging task, particularly in outdoor scenarios. Among the literature proposals to mitigate this problem, we highlight semantic clustering as a recent energy-efficient technique for prolonging the network lifetime. In semantic clustering, each cluster has a semantic leader (collector) which is periodically elected according to an energy-related criterion. However, since collectors’ energy depletion is faster than the others members of their cluster, suitable election mechanisms are required to avoid the energy hole problem. Here we propose FLECHA, a mechanism based on the ARIMA model to predict semantic collectors elections with leader-node alternation. Our hypothesis is that by anticipating the best candidates to semantic leaders, we can improve the energy-saving at the node-level, and hence allow the network lifetime to be further extended.